2022
DOI: 10.3390/jcm11237216
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury and Acute Kidney Injury—Outcomes and Associated Risk Factors

Abstract: Our objective was to analyze the contribution of acute kidney injury (AKI) to the mortality of isolated TBI patients and its associated risk factors. Observational, prospective and multicenter registry (RETRAUCI) methods were used, from March 2015 to December 2019. Isolated TBI was defined as abbreviated injury scale (AIS) ≥ 3 head with no additional score ≥ 3. A comparison of groups was conducted using the Wilcoxon test, chi-square test or Fisher’s exact test, as appropriate. A multiple logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The secondary complications such as AKI in patients with TBI portend a poor prognosis. Barea-Mendoza et al [6] found that the occurrence of AKI in patients with TBI was associated with increased mortality. Several studies have reported the correlation between serum magnesium and AKI risk in patients with other diseases, such as cardiac surgery patients [14], malignancy patients [12], and critically ill children [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary complications such as AKI in patients with TBI portend a poor prognosis. Barea-Mendoza et al [6] found that the occurrence of AKI in patients with TBI was associated with increased mortality. Several studies have reported the correlation between serum magnesium and AKI risk in patients with other diseases, such as cardiac surgery patients [14], malignancy patients [12], and critically ill children [23].…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is common after brain injury, with an incidence of 10% in patients with TBI [5]. Several studies have reported that patients with TBI who develop AKI are associated with a longer length of stay and an increased risk of mortality [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Myoglobin-associated rhabdomyolysis and renal toxicity should be considered in patients with TBI. A recent multicenter registry study found rhabdomyolysis present in 3.8% of patients with TBI and independently associated with AKI occurrence [ 54 ]. Moreover, while rhabdomyolysis and elevated serum/urinary myoglobin correlate with AKI occurrence, they also correlate with trauma severity and other renal insults.…”
Section: Aki Causes and Pathophysiological Mechanismsmentioning
confidence: 99%
“…A growing amount of attention is being given to brain-kidney interactions, and some studies have explored the association between TBI and kidney dysfunction, with the majority of the research focusing on the relationship between TBI and post-traumatic acute kidney injury (AKI) ( 7 , 8 ). Although the mechanisms are not fully understood, potential factors contributing to TBI-induced AKI include post-injury inflammation and the dysregulation of catecholamine release ( 9 ).…”
Section: Introductionmentioning
confidence: 99%